Kampung Inhabitant Economic and Social Life Improvement as a Result of Inserting Creativity - Nur Dini, Sharfina; Sihombing, Antony (International Journal of Engineering and Technology, 2019)
This paper study about thematic kampung in Semarang that is a government projectÂ  to overcome poverty, social, and economic problem in the city that majority was caused by middle class housing. This research was analyzed using some method, such as literature study, site visit to Kampung Batik, Kampung Pelangi, and Kampung Jawi in Semarang that has different location, contour, and culture, interview with kampung inhabitants, documentation, and architectural sketch. Data collection was based on literature study that studying about kampung as a part of the city, site morphology, kampung typology, inhabitant relation with their dwelling place, and creativity in kampung that affect the inhabitant social and economic life. This study finds that creativity changes in kampung affect inhabitant happiness caused by their kampung transformation that becoming more beautiful and comfortable. Tourists that come into inhabitant kampung make them more aware about their kampung. They keep kampung cleanliness and continue to make improvement of their kampung. Kampung creativity also can raise inhabitant economic value by bringing tourist into the kampung. Based on this study, this paper suggests that inhabitant kampung needs to keep their kampung cleanliness and creativity as time changes. Government also needs to help the kampung inhabitant byÂ  making kampung improvement project and giving donation and support based on inhabitant needs.Â